Effect of Compatibilizing Agents on Organoclay Dispersion of Polypropylene/Organoclay Nanocomposites - Zaman, Haydar; Khan, Ruhul Amin (Progress in Applied Science and Technology, 2021)
The purpose of this research was to observe the effect of two compatibilizers, namely, maleated polypropylene (denoted as PPM) and potassium succinate-g-polypropylene (denoted as PPK), on the properties of polypropylene (PP)/PPM/organoclay (OC) or PP/PPK/OC ternary nanocomposite. Nanocomposites were made by melt blending PP directly with 5 wt% organoclay (Cloisite 15A, OC) using two separate compatibilizers with a fixed amount of 10 wt%. Transmission electron microscopy (TEM) photographs confirmed that the OC was intercalated and exfoliated within the presence of PP/PPM or PP/PPK during melt mixing. PPK compatibilized systems had better exfoliation of PP/OC nanocomposites than PPM compatibilized systems. Better dispersion and exfoliation state of OC was performed by adding PPK rather than PPM. PP/PPK/OC nanocomposites were found to have the most continuous and uniform size. The PPK compatibilized system has given higher tensile strength and tensile modulus but with less elongation at break (%) than in PPM compatibilized cases. Differential scanning calorimetry (DSC) assessment indicates an increase in melting temperature, crystallization temperature, and crystallinity. Moreover, the addition of PPK or PPM with OC enhances the rheological behaviors of nanocomposites.